A válságos évtizedek világa magyar katonaszemmel : a magyar tisztikar földrajzi képe a két világháború között - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2016)
One of the reoccurring notions of universal and Hungarian military history is that Hungary entered World War II militarily unprepared, or at least inappropriately prepared. It is a historical fact that the contemporary political elite, including the military leadership, was racing against time when the war broke out in 1939 and the Hungarian armed forces had to be developed at a frantic pace. However, military historiography mostly ignored the Hungarian career military officers’ professional preparedness and knowledge of geography. The latter fundamentally governs the operation of military forces and geographical knowledge of the world also influences decisions of military politics. The crucial military geographical knowledge in this case consists of two factors: the standard of military geography as a discipline and the worldview of civilian professionals. The present study intends to reconstruct these two elements based primarily on contemporary military periodicals. However, the assessment of the standard of this knowledge – from a methodological aspect – cannot be reduced to the period between the two World Wars, as the leadership of generals and military officers received its geographical education in the military school system of the Austro-Hungarian Empire. Thus, the study needs to be extended to the period between 1867 and 1918 as well.